2012
DOI: 10.1111/j.1559-1816.2011.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Education on Attitudes toward Affirmative Action: The Role of the Policy's Strength

Abstract: The present research examined the influence of education on attitudes toward affirmative action. Studies 1 and 2 showed no impact of education on attitudes toward “soft” policies of affirmative action. In contrast, they showed less support of the more educated to “hard” policies of affirmative action. Neither prejudice (Study 2), nor understanding of the affirmative-action policies (Study 3)accounted for this effect. Study 4 demonstrated that the education effect is mediated by the threat posed by strong plans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Relatedly, these people possess a more pronounced sense of being in control of their fate (Kraus, Piff, & Keltner, 2009). Not surprisingly, this self-focus is associated with beliefs in meritocracy, low awareness of social inequalities, and low concern for other people (Faniko et al, 2012;Kraus et al, 2011). The reverse pattern of findings emerges on collectivistic behaviors.…”
Section: The Social Class Dividementioning
confidence: 96%
“…Relatedly, these people possess a more pronounced sense of being in control of their fate (Kraus, Piff, & Keltner, 2009). Not surprisingly, this self-focus is associated with beliefs in meritocracy, low awareness of social inequalities, and low concern for other people (Faniko et al, 2012;Kraus et al, 2011). The reverse pattern of findings emerges on collectivistic behaviors.…”
Section: The Social Class Dividementioning
confidence: 96%
“…Second, QBs try to assimilate into the higher‐status group (i.e., men) by emphasizing their stereotypically masculine characteristics and leadership qualities. Finally, QBs have been found to legitimize the current status quo in which men have higher status than women by opposing policies that would improve the standing of women (Derks et al, in press; Derks, Van Laar, et al, ; Derks, Van Laar, Ellemers, & Raghoe, ; Faniko, ; Faniko, Lorenzi‐Cioldi, Buschini, & Chatard, , ; Faniko et al, ; Ng & Chiu, ).…”
Section: The Origins Of the Qb‐phenomenonmentioning
confidence: 99%
“…Second, research demonstrates that being a member of a disadvantaged group can determine attitudes towards quotas and affirmative action policies targeting other disadvantaged groups. Kane and Whipkey () demonstrated that support for gender‐based affirmative action is not only predicted by gender, but also by being an ethnic minority or being of lower education (see also Faniko, Lorenzi‐Cioldi, Buschini, & Chatard, ), such that minority group members are more likely to report supportive attitudes. These differences are particularly pronounced for strong policies such as quotas (see Harrison et al, ).…”
Section: What Predicts Attitudes Towards Quotas and Affirmative Action?mentioning
confidence: 99%
“…Evidence from experimental studies back up this claim. Faniko et al () demonstrated that those who were highly educated demonstrated stronger support for a system in which everyone gets rewarded according to their individual performance (the importance of meritocracy), which in turn increased their opposition to the policy. Similar effects have been found for constructs closely related to meritocratic beliefs such as stratification beliefs (i.e., beliefs that wealth and power is distributed because of the actions of individuals or because of structural mechanisms; Kane & Whipkey, ) and system justification beliefs (i.e., the belief that the current system is fair; Phelan & Rudman, ).…”
Section: What Predicts Attitudes Towards Quotas and Affirmative Action?mentioning
confidence: 99%